Clinical relevance of macromolecular complexes involving integrins, potassium and sodium ion channels and the sodium/proton antiporter in human breast cancer - Elena Lastraioli; Jessica Iorio; Francesco Piazza; Chiara Capitani; Michele Santillo; Claudia Duranti; Simonetta Bianchi; Icro Meattini; Scott P. Fraser; Mustafa B. A. Djamgoz; Andrea Becchetti; Annarosa Arcangeli (Cancer Cell International)
Abstract Background Mounting evidence underline the relevance of macromolecular complexes in cancer. Integrins frequently recruit ion channels and transporters within complexes which behave as signaling hubs. A complex composed by β1 integrin, hERG1 K+ channel, the neonatal form of the Na+ channel NaV 1.5 (nNaV1.5) and the Na+/H+ antiporter NHE1 (NHE1/hERG1/β1/nNaV1.5 complex) has been recently described to be expressed and regulate relevant cancer related behaviors in Breast Cancer (BCa) cells. Methods We analyzed the expression and impact on outcome of the genes encoding the four proteins forming the NHE1/hERG1/β1/nNaV1.5 complex (SLC9A1, KCNH2, ITGB1 and SCN5A) in public datasets. The corresponding proteins were also evaluated by immunohistochemistry and their expression was correlated with clinic-pathological and molecular characteristics and patients’ survival. Results The expression of KCNH2 and SCN5A was significantly correlated in primary BCa as occurs in the heart, although with a broader distribution, forming a functional network which also included ITGB1 and SLC9A1. The co-expression proteins emerged from the immunohistochemistry analysis. Interestingly, hERG1, nNav1.5 and the hERG1/β1 integrin complex associated with several clinical features, including molecular subtype and hormone receptor status. Moreover, hERG1 and the combination of hERG1 and nNav1.5 had impact on prognosis, contributing to identifying a group of patients with worse prognosis. Conclusions hERG1 and nNav1.5 channels along with β1 integrins and the NHE1 antiporter are co-expressed in BCa both at gene and protein levels, assembling into a macromolecular complex. The NHE1/hERG1/β1/nNaV1.5 complex can be considered a novel biomarker and potential target for therapy for BCa patients.